The multifaceted role of vitreous hyalocytes: Orchestrating inflammation, angiomodulation and erythrophagocytosis in proliferative diabetic retinopathy - Stefaniya K. Boneva; Julian Wolf; Malte Jung; Gabriele Prinz; Toco Y. P. Chui; Jacqueline Jauch; Anne Drougard; J. Andrew Pospisilik; Anja Schlecht; Felicitas Bucher; Richard B. Rosen; Hansjürgen Agostini; et al. (Journal of Neuroinflammation)
Abstract Background Despite great advances in proliferative diabetic retinopathy (PDR) therapy over the last decades, one third of treated patients continue to lose vision. While resident vitreous macrophages called hyalocytes have been implicated in the pathophysiology of vitreoretinal proliferative disease previously, little is known about their exact role in PDR. In this study, we address molecular and cellular alterations in the vitreous of PDR patients as a means towards assessing the potential contribution of hyalocytes to disease pathogenesis. Results A total of 55 patients were included in this study encompassing RNA-Sequencing analysis of hyalocytes isolated from the vitreous of PDR and control patients, multiplex immunoassay and ELISA analyses of vitreous samples from PDR and control patients, as well as isolation and immunohistochemical staining of cultured porcine hyalocytes. Transcriptional analysis revealed an enhanced inflammatory response of hyalocytes contributing to the cytokine pool within the vitreous of PDR patients by expressing interleukin-6, among others. Further, increased angiopoietin-2 expression indicated that hyalocytes from PDR patients undergo a proangiogenic shift and may thus mediate the formation of retinal neovascularizations, the hallmark of PDR. Finally, RNA-Sequencing revealed an upregulation of factors known from hemoglobin catabolism in hyalocytes from PDR patients. By immunohistochemistry, cultured porcine hyalocytes exposed to red blood cells were shown to engulf and phagocytose these, which reveals hyalocytes’ potential to dispose of erythrocytes. Thus, our data suggest a potential role for vitreous macrophages in erythrophagocytosis and, thereby, clearance of vitreous hemorrhage, a severe complication of PDR. Conclusion Our results strongly indicate a critical role for vitreous hyalocytes in key pathophysiological processes of proliferative diabetic retinopathy: inflammation, angiomodulation and erythrophagocytosis. Immunomodulation of hyalocytes may thus prove an essential novel therapeutic approach in diabetic vitreoretinal disease.